(untitled) (Revista de História da UEG (REVHIST), 2022)
The purpose of this article is, first of all, to approach the theme of the scandal in the Portuguese Inquisition. An important element in the opening and closing dynamics of sodomy processes, the scandal is approached from a historical point of view, focusing on the social dimensions that some cases involved. Secondly, with a more specific aim, it is intended to explore the relationships established between the scandal and the social organizations of the Ancien Regime. Methodologically anchored in the perspective of Micro-History, this article recovers the social relations of tension and conflict typical of the Ancien Régime and privileges the denunciations and confessions that span the years from 1567 to 1660. Keywords: Scandal. Sodomy. Inquisition.